Bilateral adrenal infarction and secondary haemorrhage in pregnancy: implications of factor V Leiden heterozygosity. A review of the literature and a case report - Wiaam Elradi; Samreen Innayat; Ahmed Hanafy; Sharifah Naseem; Abuzar Awadelkareem; Deepika Meneni (Clinical Medicine)
Adrenal haemorrhage in pregnancy is rare but can lead to significant maternal and fetal morbidity if unrecognised. We present the case of a 25-year-old woman in her second pregnancy, who was admitted at 34 + 4 weeks of gestation with severe abdominal pain. Despite initial unremarkable assessments, further imaging revealed a left adrenal haemorrhage, with evidence of prior right adrenal infarction, resulting in primary adrenal insufficiency. Haematological investigations later confirmed heterozygous factor V Leiden as a likely contributing factor. This report underscores the diagnostic challenges of adrenal pathology in pregnancy, where symptoms may overlap with more common conditions. Immediate management with hydrocortisone therapy, supported by a multidisciplinary team (MDT), was employed, with a successful outcome for both mother and child following delivery by caesarean section.